High Density Lipoproteins Induce Cell Cycle Entry in Vascular Smooth Muscle Cells Via Mitogen Activated Protein Kinase-dependent Pathway - Nofer, Jerzy-Roch; Junker, Ralf; Pulawski, Ewa; Fobker, Manfred; Levkau, Bodo; Eckardstein, Arnold von; Seedorf, Udo; Assmann, Gerd; Walter, Michael (Thrombosis and Haemostasis, 2001)
In this study we found that HDL acts as a potent and specific mitogen in vascular smooth muscle cells (VSMC) by stimulating entry into S-phase and DNA synthesis in a time- and concentration-dependent manner, induction of cyclins D1, E, and A, as well as activation of cyclin D-dependent kinases as inferred from phosphorylation of the retinoblastoma protein (pRb). Moreover, HDL induced activation of the mitogen-activated protein kinase pathway including Raf-, MEK-1, and ERK1/2, as well as the expression of proto-oncogen c-fos, which is controlled by ERK1/2. PD98059, an inhibitor of MEK-1 blocked the mitogenic activity of HDL and cyclin D1 expression. HDL-induced VSMC proliferation, cell cycle progression, cyclin D1 expression, and activation of the Raf-1/MEK-1/ERK1/2 cascade were blocked by pre-incubation of cells with pertussis toxin indicating involvement of trimeric G-protein. By contrast, none of these responses was inhibited by the protein kinase C inhibitor, GF109203X. The mitogenic effects of native HDL were not mimicked by apo A-I, reconstituted HDL containing apo A-I, or cholesterol-containing liposomes. In conclusion, HDL possesses an intrinsic property to induce G-protein- and MAP-kinase-dependent proliferation and cell cycle progression in VSMC. The strong and specific mitogenic effect of HDL should be taken into account, when therapeutic strategies to elevate the plasma level of these lipoproteins are developed.
Keywords: High density lipoproteins; smooth muscle cells; signal transduction; arteriosclerosis